2017
DOI: 10.1590/0103-8478cr20170011
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Multispecies Biofilms by Escherichia coli, Staphylococcus aureus, and Salmonella spp. Isolated from Raw Fish and a Fish Processing Unit

Abstract: The consumption of fish by the Brazilian population is increasing. However, fish and seafood are highly perishable and can be contaminated with several microorganisms. In addition, the possibility of biofilm formation is a greater cause for concern. In this study, biofilm formation was evaluated in single- and multispecies cultures at 25°C for incubation periods of 0, 4, 8, 24, and 48h in stainless steel coupons (size, 1.0×1.0cm) immersed in tryptic soy broth. The characteristics of the formed biofilms after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
(4 reference statements)
2
6
0
Order By: Relevance
“…Considering this parameter, both E. coli O157:H7 sushi isolate and the control strain (NCTC 12900) had the ability to form biofilms with concentrations above 5 log CFU per cm of cells adhered to the stainless steel coupon at all temperatures tested in this study. Frozi et al () found biofilm counts in stainless steel of 7 log CFU per cm after 24 h of incubation at 25°C, using E. coli non‐O157 isolates from raw fish and from a fish processing unit, a similar result to that obtained in this study at temperatures of 25 and 37°C.…”
Section: Discussionsupporting
confidence: 88%
“…Considering this parameter, both E. coli O157:H7 sushi isolate and the control strain (NCTC 12900) had the ability to form biofilms with concentrations above 5 log CFU per cm of cells adhered to the stainless steel coupon at all temperatures tested in this study. Frozi et al () found biofilm counts in stainless steel of 7 log CFU per cm after 24 h of incubation at 25°C, using E. coli non‐O157 isolates from raw fish and from a fish processing unit, a similar result to that obtained in this study at temperatures of 25 and 37°C.…”
Section: Discussionsupporting
confidence: 88%
“…The suppressive action Salmonella in dual biofilm formation was also described by Esteves et al [48] and described the poor outcompete manner of E.coli over the Salmonella strains. The significantly less biofilm-forming ability of SAL 1+SAL 3 as dual culture also corroborates with previous findings of Gkana et al [49] and Frozi et al [50], who speculated the lower biofilm-forming ability of Salmonella as dual cultures. However, the observed low biofilm capabilities or same biofilm capabilities of Salmonella and its interaction in different time points (Table 3) may be due to strain-dependent different properties, such as EPS production, presence of either flagella or fimbriae, etc.…”
Section: Interaction Of Salmonella 1 (Sal1) With Salmonella 3 (Sal 3) Proteus and E Coli In Dual Biofilm Formationsupporting
confidence: 91%
“…According to the review of literature, Escherichia coli, a gram-negative bacterium, is one of the most versatile microorganisms reported in nature, contributes to form biofilm easily on the different surfaces of food industry (Frozi et al 2017). Similarly, Bacillus subtilis is a grampositive soil bacterium that is constantly exposed to a broad range of environmental stresses (Borriss et al 2018) and can respond to stressful conditions by forming biofilm on different surfaces (Romero et al 2010).…”
Section: Introductionmentioning
confidence: 99%